Critical Thinking About History<subtitle>Swedish Teenagers Read Holocaust Fiction</subtitle> - Linnea Bladfors; Lydia Kokkola (Barnelitterært Forskningstidsskrift)
Fiction is often incorporated into the teaching of history in Swedish high schools. However, critical thinking skills are required in order to distinguish historical truths from the artistic freedom of fiction, not least because types of data that constitute historical evidence frequently lack information about the thoughts, feelings and beliefs of the people involved. In providing such elements, literature may either distort understanding of the past or help to develop the critical thinking skills needed when considering historical evidence. This paper includes an empirical examination of how six Swedish teenagers responded to Markus Zusakʼs novel, The Book Thief. The interviews revealed that Zusakʼs narrative style affords critical thinking, but also that collective reasoning and guidance are needed.